Characterization of Electric Field Profile for C4F7N with CO2 Under Different Electrode Configurations - Ahmed, Rizwan; Abd Rahman, Rahisham; Abd Latif, Nur Najihah (Evolution in Electrical and Electronic Engineering, 2022)
This research work focuses on the effect of electric field distribution in C4F7N dielectric gas under different electrode configurations and varying air gap distances. Finite Element Analysis (FEA) is used to simulate the model in axial-symmetrical. Different electrode configurations such as sphere-sphere, plane-plane, rod-rod, rod-plane, and rod-sphere are utilized to analyze the effect of electric field distribution and breakdown of the proposed gas. It is concluded that the distance between the electrodes significantly impacts the distribution of the electric field in the gap. Shorter the gap distance, the stronger the electric field. The electrode geometry also affects the electric field distribution. The stronger field is observed at the center in sphere-sphere configuration, while in the case of plane-plane configuration, the field intensity is stronger than the sharp edges of the plane electrode.